“When my priestly lips say secret words”: ‘Abraxas’, magic and politics in the Greek magical papyri - Diblasi Neto, Ítalo (Romanitas - Revista de Estudos Grecolatinos, 2015)
The paper investigates a selection of spells from the Greek Magical Papyri in which the cock-headed god Abraxas appears. Reconstructing the historical process of finding and compilation of the Papyri, the article examines the magical context of the Mediterranean world in the first III centuries E.C., the overall aspects of the magical beliefs contained in these texts and the power relations established between those who practiced magic and the institutions of a social context that never approved it.